Polytherapy and drug interactions in elderly - Gujjarlamudi, Hima Bindu (J Midlife Health, 2016)
There is an increase in population of elderly above the age of 65. As age advances, more diseases develop resulting in use of more medications. Physiological changes, alterations in homeostatic regulation and diseases modify pharmacokinetics and drug response in older patients. The risk for drug interactions and drug-related problems increases along with multiple medications. Periodic evaluation of the patients’ drug regimen is essential to minimize polytherapy. Clinicians must be alert to the use of herbal and dietary supplements as they are prone to drug-drug interactions. This article focuses on the possible pharmacokinetic, pharmacodynamic, and herbal drug interactions occurring in the elderly.